Sistemas Silvipastoris com frutíferas para recria de bezerras leiteiras : implantação e estabelecimento - Giustina, Carolina Della (2016)
A strategy to reduce the heat stress in dairy calves is providing natural shade. Silvopastoral systems can improve these conditions and also the farm‟s income by the fruit production. However, the system establishment phase is the most critical moments, it is necessary to avoid competition between the fruit seedlings and species already established in the area that become undesirable under its canopy. Papers on the interaction between plant components, trees and forage in a silvopastoral system are scarce. When the arboreal component is a fruit tree, these are practically non-existent in the literature. Therefore, the objective of this study was to evaluate the interaction between fruit trees and the Tifton-85 (Cynodon spp.) in silvopastoral system during the establishment phase. The experiment was conducted at Embrapa Agrosilvopastoral, Sinop - MT, Brazil. The treatments were eight species of fruit trees intercropped with Tifton-85: yellow mombin (Spondias mombin), red guava (Psidium guajava) cv. Paloma, cashew (Anacardium occidentale) cv. Embrapa 51 (EMB51) and cashew cv. CCP 76, acerola fruit (Malpighia glabra) cv. Roxinha and acerola fruit var. Sertaneja, green-coconut (Cocos nucifera L.) and banana (Musa spp.) cv. Williams. The experiment was carried out during the period from January until June 2015. The systems were planted 15 months before the start of sampling. We evaluated: the fruit trees growth, the light environment and the vegetal material production under the canopy. Data were analyzed with SAS 9.2, considering a 5% probability of erros level. The guava fruit trees grew more than other fruit trees, but showed lower LAI and LI values and higher R/Fr relation, allowing more plant under its canopy. Yellow mombin trees had a similar response however, this specie is deciduous, had limited use in integrated system because this kind of tree does not protect the animals against the sun during the dry season. Banana trees and coconut showed a strong dependence of extra water supply during the dry season. The remaining species showed an adequate growth and potential to control plant species growth under their canopy, establishing quickly in integrated systems.